Pengkajian Cepat Kesehatan Lingkungan pada Manajemen Bencana - Aam Amirudin; Syamsul Maarif; Christin Sri Marnani; Wilopo Wilopo (HB PRESS, 2021)
Disasters that often occur in Indonesia have a very large impact that affects various aspects of people's lives who experience it, this is due to damaged health facilities and the incidence of morbidity, both during and after the disaster. This condition requires concrete efforts in the form of organized and programmed disaster management so as to minimize the impacts that occur with various approaches based on real field data, Rapid Empironment Health Assessment (REHA) is an action effort for disaster management that can be carried out. by collecting data from disaster areas with reference to environmental health aspects, this aspect has a very large influence considering the environmental health consequences that are not handled will cause high morbidity and even the potential for outbreaks, from the data obtained in the field can take more policy disaster management actions accurate and on target because it refers to the real needs of the community affected by the disaster, this paper is expected to be a reference for field officers in carrying out quick vicious actions in the field of environmental health in the event of a disaster to immediately collect data in the context of recommendations to determine future action plans during disaster emergency response, This can improve the sustainability of the lives of people who experience disasters by meeting their needs in a standard manner even in disaster conditions so that safe conditions for the community will emerge from the trauma of a daisies disaster. focus on maintaining national welfare and security